Labor Regulations and the Cost of Corruption: Evidence from the Indian Firm Size Distribution - Amirapu, Amrit; Gechter, Michael (The Review of Economics and Statistics, 2020)
In this paper, we estimate the costs associated with an important suite of labor regulations in India by taking advantage of the fact that these regulations apply only to firms above a size threshold. Using distortions in the firm size distribution together with a structural model of firm size choice, we estimate that the regulations increase firms' unit labor costs by 35%. This estimate is robust to potential misreporting on the part of firms and enumerators. We also document a robust positive association between regulatory costs and exposure to corruption, which may explain why regulations appear to be so costly in developing countries.